Analisis Pengaruh Gaya Kepemimpinan Kepala Sekolah Terhadap Motivasi Kerja Guru dan Tendik (Sindoro: Cendikia Pendidikan, 2025)
This study aims to determine the influence of the principal's leadership style on teachers' work motivation. School principals have a strategic role in creating a work environment that supports performance. The population in this study is teachers and staff of private junior high schools in Ngamprah District, West Bandung which totals 148 people, samples are taken using the slovin formula with an error rate of 5% thus the number of samples in the study is 108 respondents. Through a quantitative descriptive approach, data was collected from a number of teachers in several schools to find out their perceptions of the principal's leadership style and their level of work motivation. The results showed that transformational and participatory leadership styles had a significant positive influence on teacher motivation, while authoritarian leadership styles tended to lower motivation levels. These findings affirm the importance of communicative, inspiring, and empowering leadership in improving teacher motivation and performance in the school environment.